Exporters' reactions to trade protectionism: Implications from the US-China trade conflict - Dr. Molly De-Luca,; Dr. Jeanmaric-Voskresensky, (Al-Qanṭara, 2023)
This study of the US-China trade conflict in 2010 aims to determine how exports react to trade protection. We find that the start of the US's trade war against Chinese exports reduces China's overall exports to the US by an average of 26.87% for the period of January 2000 to May 2023. Further analysis reveals that the decline in exports is primarily attributable to a drop in quantity, with prices remaining largely unchanged. Negative trade shocks also drive exports in R&D-intensive, skilled labor-intensive, high- apital-income-share, and upstream industries to be routed even more to nearby nations with larger economies. Industries with a comparative advantage, rapid export growth, high export value, and high elasticity of substitution, according to heterogeneous analyses. Keywords- Trade war, China, US and conflict